Investigation of the process of smoothing with ultrasound - Тurych Valery; Rutkevych, Volodymyr; Goncharuk, Natalia; Ogorodnichuk, Galina (Eastern-European Journal of Enterprise Technologies, 2018)
We studied and simulated the ultrasonic smoothing process. We carried out the analysis of the contact interaction of a tool with a part in the process of ultrasonic smoothing with a preceding gap. The analysis provides an opportunity to calculate a change in a size of a part during the treatment depending on modes. We derived the dependences of a contact area at the ultrasonic smoothness with a preceding gap. We performed the experimental study of an influence of parameters of the process of ultrasonic smoothing on parameters of a quality of a surface layer of a part. We established that in order to ensure the required roughness and accuracy, the depth of introduction should not exceed 7 μm, especially when treated parts are made of materials with a low modulus of elasticity. We developed an installation for experiments based on the high precision automatic screw machine 16B05АF10. All additional devices and tools were attached to the tool holder of a given machine. We developed a technique to measure the time of contact between a tool and an article under ultrasonic smoothing with a preceding gap. We established that deformation of micro roughnesses occurs due to a pressure of projections of micro roughnesses to cavities since we excluded shift deformation by using a solid lubricant. The fact that there was no texture on the microsection of the treated surface, although we could observe hardening of a surface, indicates that there is no shift deformation. Based on this conclusion, it is possible to disregard a non-contact wave of deformation. We obtained analytical dependences of contact area under ultrasonic smoothness with a preceding gap on treatment parameters, namely, the treatment speed, the feed rate, the radius of an operation surface of a tool. The results of mathematical modeling and experimental data are quite close. We defined the region of optimal feed, which makes it possible to obtain surfaces with minimal roughness or microrelief.